Application of DTI and fMRI in moyamoya disease - Hao, Xiaokuan; Liu, Ziqi; He, Shihao; Wang, Yanru; Zhao, Yuanli; Wang, Rong (Frontiers in Neurology, 2022)
Moyamoya disease (MMD) is a chronic and progressive cerebrovascular stenosis or occlusive disease that occurs near Willis blood vessels. Diffusion tensor imaging (DTI) and functional magnetic resonance imaging (fMRI) are used to detect the microstructure of white matter and the function of gray matter, respectively. The damage of these structures will lead to the change of cognitive level in patients with moyamoya disease. In this paper, the principles of DTI and fMRI, their applications and challenges in moyamoya disease are reviewed.